Propuesta para la creación de la Dirección Técnica de Turismo para fortalecer la actividad turística del Gobierno Autónomo Descentralizado del cantón San Miguel provincia Bolívar año 2019 - Ocampo Gavilanes, Shirley Ayde (2020)
This research project was carried out with the purpose of proposing the creation of the Technical Directorate of Tourism in the San Miguel canton of the Bolivar province, through a participatory analysis with the Decentralized Autonomous Government of the canton and tourism service providers for tourism strengthening , the design of the legal structure was made an ordinance model that allows the implementation of the Technical Directorate of Tourism, also defined the administrative structure establishing what will be the mission, vision, objectives, policies, structural and functional organization chart, programs and projects with Those who are going to have this department also established what will be the mechanisms for transferring tourism skills, an economic and financial study was carried out to identify the costs, benefits of this proposal. For the evaluation, at this stage all those elements that the financial study itself must provide with an initial value of $ 15,762 were defined to help tourism management, relationship and control. To implement this department, it will be done under the resolution of the Municipal Council, finally this proposal will be viable since the San Miguel canton has natural attractions and cultural manifestations that can strengthen the tourism sector of the province. Keywords: Technical Directorate of Tourism, Decentralization, administration